Towards the contextualisation of democracy: A critical precursor for citizenship education in universities - Davids, N. (South African Journal of Higher Education, 2019)
In response to a controversial article, which sought to draw connections between intelligence and essentialist understandings of race and ethnicity, a university Senate has adopted a motion, geared at off-setting any future research of this nature. The resort to notions and imperatives of citizenship education, as contained in this motion, raises necessary questions about how a university conceives of itself in relation to acting and being democratic. It would appear from the language and content of the motion, that should the motion be implemented, it risks slipping into yet another reductionist approach to citizenship education. In response, this article argues that citizenship education cannot be decontextualized from the space (a university) in which it is expected to function and live. That is, that democratic citizenship education can only be meaningful to the extent that the principles and values are democracy are brought forth through the lived experiences of students, academics, and all others, who occupy this space.